N12 Development and introduction of a pre-clinic screening, triage system and virtual consultations for patients with Inflammatory Bowel Disease: a nurse led quality improvement project (QIP). (30th January 2023) - Gleeson, S; Buckley, P M; McCarthy, D J; Sugrue, K; O'Grady, D J; O'Sullivan, C; O'Sullivan, G; Naughton, C
Abstract: Background: In the IBD centre, Mercy University Hospital( MUH), all patients (Approximately 4000 patients with IBD) attend the outpatient clinic for face-to-face consultations as per prescheduled appointments regardless of disease status. Mismatch between need and access to care. Patients in remission attend for elective appointments, while patients in need of urgent specialist review may have to wait or else attend clinics which are already at capacity as an urgent appointment. The increasing strain on the OPD system calls for new models of care to be explored. Aim :develop and implement a pre-clinic screening, triage system and virtual consultations for low-risk patients & evaluate the impact on patient reported and health service outcomes. Prioritise patients with more unstable IBD symptoms for face-to-face consultations, while for patient with stable IBD to increase consultation choice (virtual or face to face) …Examine impact on patient experience …Examine impact on OPD waiting lists Methods: QIP conducted over a 6 month period. 1980 patients included in the study. 1560 patients were scheduled to attend OPD in the 6month timeframe and 420 patients were on the IBD OPD waitlist for return/ first time consult. logic model planning and PDSA cycles to develop, test, refine and implement; 1.A pre-clinic screening, assessment and triage pack to assess patients clinical status and education needs 2.Inclusion and exclusion criteria for virtual consultations 3.Clinic pathway algorithms 4.Weekly virtual IBD MDTs Results: 95% of patients completed the pre-clinic screening and triage pack, of these 37% were eligible for telephone consultation and 89% of those deemed eligible were happy to switch from face to face to telephone consultation. 30% of patients who attended for pre-clinic screening and triage assessment required fast tracking of OPD appointments due to unstable disease and received earlier interventions e.g. colonoscopies, MRI's and medication optimisation. IBD waiting list of 420 patients was cleared with this initiative, all patients were offered a telephone or OPD consultation based on the result of the pre-clinic triage assessment and patient preference. 83% of patients would be happy to continue with the new model as it was perceived as more convenient, time efficient and less disruptive to everyday life. Conclusion: This study highlighted that virtual management of IBD is acceptable to patients, significantly decreased clinic visit utilisation and can reduce the growing burden of IBD on health care resources .This initiative had many positive organisational outcomes including the elimination of the IBD OPD waiting list, reduction in non-essential clinic attendances and potential cost savings.